SOCIAL PRESENCE AND SOCIAL ABSENCE: SOCIO-CULTURAL PRODUCTION OF SELF IN ONLINE LEARNING ENVIRONMENTS - Oztok, Murat (AoIR Selected Papers of Internet Research, 2014)
The concept of social presence has long been employed to study identities in online learning environments. However, the process of identification in digitally-mediated experiences is not only articulated by what is represented but also defined by what is filtered-out in that particular representation. I shall term these consciously filtered-out identifications social absence. Therefore, I regard social absence as the extent to which particular identifications are not represented in one’s social presence. The idea of social absence suggests that individuals may hide behind their relative anonymity. This research, therefore, introduces the concept of social absence and illustrates the ways individuals experience social absence in online learning.